Critical Care Trainees’ Career Goals and Needs: A Canadian Survey - Maude St-Onge; Keren Mandelzweig; John C Marshall; Damon C Scales; John Granton (Canadian Respiratory Journal)
BACKGROUND: For training programs to meet the needs of trainees, an understanding of their career goals and expectations is required.